2011
DOI: 10.15232/s1080-7446(15)30470-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of various fatty acids on dairy calf performance

Abstract: The effect of various fatty acids on calf performance was evaluated in 3 trials. In trial 1, calves were fed a milk replacer with all animal fat or a blend of fats and with or without a blend of butyrate, medium-chain fatty acids, and linolenic acid (NeoTec4, Provimi North America, Brookville, OH) in a 2-by-2 factorial arrangement. Calf ADG, starter intake, feed efficiency, hip width change, and serum titers to bovine viral diarrhea and parainfluenza 3 vaccines were greater (P < 0.05) in calves fed NeoTec4. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 27 publications
3
39
0
Order By: Relevance
“…The use of oil from soybeans might have a negative effect on the diet because of its high concentration of linoleic acid. This was demonstrated in both the MR and starter trials of Hill et al (2011). Adding linoleic acid via soybean oil to diets elicited an inflammatory response in calves that contributed to the reduction in ADG.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…The use of oil from soybeans might have a negative effect on the diet because of its high concentration of linoleic acid. This was demonstrated in both the MR and starter trials of Hill et al (2011). Adding linoleic acid via soybean oil to diets elicited an inflammatory response in calves that contributed to the reduction in ADG.…”
Section: Introductionmentioning
confidence: 82%
“…Adding roasted soybeans to starters decreased starter intake and ADG in calves less than 2 mo of age when compared with lower-fat starters (Kuehn et al, 1994). Similarly, Hill et al (2011) reported that soy oil added to starters before 2 mo of age and fed in approximately 0.66 kg of MR between 2 and 4 mo of age reduced ADG of calves compared with lower-fat starters. More recently, Araujo et al (2014) reported that starters with soybeans were useful to provide extra energy and support additional ADG when MR were fed at approximately 0.69 but not 0.46 kg of DM daily.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…For example, Hill et al (2016) fed NeoTec5g to male calves over 8 wk and found fewer abnormal fecal score days (fecal consistency score > 2; modified from Kertz and Chester-Jones, 2004) for those provided the supplement compared to those without the supplement. In contrast, Hill et al (2011a) fed NeoTec4 to male calves for 8 wk and found no differences in abnormal fecal scores between treatments. Authors suggested that this lack of difference may have been driven by an overall lack of abnormal fecal days (average < 1 d per calf).…”
Section: Discussionmentioning
confidence: 84%
“…There was no impact of our interventions on diarrhea in veal calves. In other studies, using a similar supplement, some studies have found reduced days with abnormal fecal scores for calves provided the supplement (Hill et al, 2007a, b;2011b;, and others have not found difference (Hill et al, 2011a). For example, Hill et al (2016) fed NeoTec5g to male calves over 8 wk and found fewer abnormal fecal score days (fecal consistency score > 2; modified from Kertz and Chester-Jones, 2004) for those provided the supplement compared to those without the supplement.…”
Section: Discussionmentioning
confidence: 94%